Modelling macroeconomic linkages in a monetary union: A West African example - David Fielding; Kevin Lee; Kalvinder Shields (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
We construct a structural macroeconometric model for member states of the West African Economic and Monetary Union. Fitting this model to annual and quarterly time series data allows us to identify the channels through which macroeconomic innovation in one country impact on other countries in the union. We also discover the extent of heterogeneity across the member states in terms of the degree of similarity of macroeconomic transmission mechanisms. This is one important element in measuring the costs of union membership for each country.
Keywords: F15; F33; 330; West African Monetary Union; structural VAR; Währungsunion; ECOWAS-Staaten